The World Bank Group Guarantee Instruments 1990-2007 : An Independent Evaluation - World Bank (Washington, DC, 2012)
This evaluation reviews the World Bank Group's (WBG's) experience with guarantee instruments during 1990-2007. Although these instruments have been an established product line of the WBG for two decades, they have not been rigorously evaluated across the World Bank, International Finance Corporation (IFC), and Multilateral Investment Guarantee Agency (MIGA). The study asks three main questions: (1) should the WBG be in the guarantee business? (2) Have guarantee instruments in the three WBG institutions been used to their potential as reflected in WBG expectations and perceived demand? And, (3) is the WBG appropriately organized to deliver its range of guarantee products in an effective and efficient manner? The challenge for the WBG is to create an environment in which guarantee and insurance products can be deployed alongside other WBG instruments in a flexible and efficient manner to meet client needs. The report concludes that maintaining the status quo, particularly in the delivery of political risk mitigation products, ought not to be an option. It suggests that WBG senior management should decide whether to take a set of collective and individually tailored actions within the current institutional structure or to adopt a new organizational structure for product delivery.